فعالية المراجعة الداخلية في تقييم وتحسين الاداء المالي للمؤسسة الاقتصادية - سباع, احمد الصالح; فردية, محمد الساسي; بن عمر, حمزة (My University, 2017)
This study aims to shed light on the role of internal audit in improving financial performance by identifying the concept of internal audit, addressing various aspects, and the procedures used in the application, then how they could contribute to the improvement of the financial performance in establishing “SOUF’ SEMOULE”. This study is descriptive in which the provision of various concepts related to internal audit and performance is processed, and then the analytical method applied, which covered a sample of Algerian enterprises active in the market which are “SOUF’ SEMOULE”. The study has concluded that applying the internal audit on scientific and guided bases contributes to the achievement of the objectives of the facility, which is achieving the maximum profits with less costs, highlighting the better level of financial performance and raising the level of competitiveness of the facility.
مذكرة ماستر تدقيق محاسبي
Keywords: الاداء المالي، قياس وتقييم، مؤسسة سوف للدقيق; Internal audit, financial performance, measuring & evaluating the financial performance, “SOUF’ SEMOULE”.